Water PH Monitoring and Control System in Aquariums Based on Internet of Things - Adry, Rifaldi; Candra, Oriza (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Indonesia is one of the countries that has the richest biodiversity in the world such as the diversity of fish species, so many people use them to keep at home as ornamental fish. However, keeping fish with various activities outside the house can result in uncontrolled fish feeding, when excessive feed is given it can affect the environment of the aquarium where the fish are kept, namely the pH value of the water. Based on this, a tool was created that can monitor the pH of aquarium water which is equipped with a control system. Taking advantage of technological advances in this era, monitoring can be done on smartphones via the WhatsApp application. The microcontroller used ESP 32, is equipped with a Wifi module for internet access, so that it can store cloud-based water pH value reading data on the twilio web. Control will be carried out with the aim of maintaining the pH value of the water in the aquarium, namely if the reading results of the pH value are not at a value of 6-8. When the pH value is too low, a liquid that can increase the pH value will be pumped into the aquarium. The same thing will be done when the pH value is high, liquid to lower the pH value will be pumped into the aquarium.